Intensi Wirausaha Mahasiswa Untuk Menciptakan Kemandirian Mahasiswa Dalam Berwirausaha - Yuyuk Liana (STIE Malangkucecwara, 2017)
The purpose of this study is to describe the entrepreneurial intentions of students consisting of demographic characteristics, personality characteristics and the characteristics of entrepreneurial students at STIE Malangkucecwara Malang. The population was 2011 class of students at STIE Malangkucecwara who had stepped 6th semester and already getting entrepreneurhip subjects (Entrepreneurship). Sample using 76 respondents. The results showed that the respondents aged 18-23 years was 85.5%, most of the sex of the respondents were male as many as 41 people or 53.9%. The personality characteristics of the items need for achievement for entrepreneurs that states could not agree as much as. Next at 72.4% of respondents stated item self-efficacy strongly agreed that 47 people or 61.8%. While the variable characteristics of entrepreneurs with a future orientation items respondents said strongly agree and 65.8% of items respondents agreed responsibilities as much as 52.6%.